Geopolitical shock, ESG and stock returns: Evidence from Nordic markets during the Russia-Ukraine war - Lundberg, Santtu (My University, 2026)
This study examines the relationship between corporate responsibility and stock market returns by using an event study methodology in the Nordic markets around the start of the Russia-Ukraine war. Corporate responsibility is measured using environmental, social and governance (ESG) scores. Responsible investing dates to 1960s but in recent decades it has gained increasing popularity among both investors and academic researchers. Substantial amount of research has examined whether portfolios with higher ESG scores generate better returns than those with lower scores. More recently, attention has focused also to the relationship between ESG scores and stock returns during periods of crisis, such as the Covid-19 pandemic. Prior literature provides mixed evidence on whether companies with higher ESG scores achieve better stock returns during crises or not. The Russia–Ukraine war provides a new context for examine this relationship. This study focuses on the Nordic markets, with a final sample of 338 publicly listed companies from Norway, Sweden, Finland, and Denmark. This study also provides a broad overview of prior research on responsible investing and stock returns during crisis periods. In the empirical analysis, cumulative abnormal returns are examined across seven different event windows. Ordinary least squares (OLS) regressions are employed, the firm-specific characteristics, industry dummy and country dummy variables are controlled. All data used in the study are obtained from the London Stock Exchange Group (LSEG) database. The results suggest a negative and statistically significant relationship between social pillar scores and stock returns. However, this relationship is observed only in the shortest event window following the outbreak of the war. In addition, results show a positive and statistically significant relationship between environmental pillar scores and stock returns in the longest post-event window. The total ESG score and governance (G) pillar do not provide statistically significant results in any of the event windows.

Tässä tutkielmassa tutkitaan tapahtumatutkimuksen avulla yritysten vastuullisuuden vaikutusta osaketuottoihin pohjoismaisilla markkinoilla Venäjän ja Ukrainan sodan alkuvaiheen ympärillä. Yritysten vastuullisuutta on mitattu yrityskohtaisilla ympäristö-, sosiaali- ja hallintopisteillä. Vastuullinen sijoittaminen juontaa juurensa aina 1960-luvulle asti, mutta viimeisen parin vuosikymmenen aikana se on nostanut suosiotaan niin sijoitusmarkkinoilla kuin akateemisessa tutkimuksessakin. Monissa tutkimuksissa on tutkittu tuottaako korkean ESG pisteiden portfoliot paremmin kuin matalammat, lisäksi ESG luokituksien yhteyttä osaketuottoihin on alettu tarkastelemaan eri kriiseissä, kuten esimerkiksi covid-19 kriisin aikana. Aikaisemmat tutkimukset ovat antaneet ristiriitaisia tuloksia siitä tuottavatko korkeamman ESG luokituksen yritysten osakkeet paremmin kriisien aikana vai ei. Venäjän ja Ukrainan sota tarjosi uuden tilaisuuden tutkia ESG luokituksen yhteyttä osaketuottoihin kriisin aikana. Tämä tutkielma keskittyy pohjoismaisille markkinoille ja lopullinen otoskoko on 338 yhtiötä, joka sisältää Norjan, Ruotsin, Suomen sekä Tanskan pörssiyhtiöitä. Tutkielmassa käsitellään laajasti vastuullisen sijoittamisen aikaisempaa kirjallisuutta sekä kriisien vaikutusta osaketuottoihin. Tutkimuksen empiirisessä osiossa osakkeiden kumulatiivisia epänormaaleja tuottoja tarkastellaan seitsemässä eri tapahtumaikkunassa. Tutkimuksessa on käytetty OLS- regressioita ja niitä on kontrolloitu useilla eri yrityskohtaisilla luvuilla, myös toimiala sekä maat on huomioitu kontrolleissa. Kaikki tutkimuksessa käytetty data on hankittu LSEG tietokannasta. Tulosten perusteella sosiaalisen vastuu luokituksen ja osaketuottojen välillä on havaittavissa negatiivinen tilastollisesti merkitsevä yhteys sodan alkamisen jälkeen lyhyimmässä tapahtumaikkunassa. Lisäksi tulokset osoittavat positiivisen ja tilastollisesti merkitsevän yhteyden ympäristö luokituksen ja osaketuottojen välillä. Tämä tulos havaitaan vain sodan alkamisen jälkeen pisimmässä tapahtumaikkunassa. Kokonais ESG- pisteet ja hallintotapa luokitus eivät osoittaneet tilastollisesti merkitseviä tuloksia minkään tapahtumaikkunan aikana.
Keywords: responsible investing; corporate responsibility; Nordic countries; Russia; crises; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance